Homeland in the poetry collection *“Present-Tense Wounds”* by Zaher Habib: A Thematic Approach - Al-Rashidi, Bairam Younes; Kouli, Asst. Lecturer Ayyoub, Haji Mohammed (El Omda in Linguistics and Discourse Analysis, 2022)
Homeland is a symbol of human existence and a marker of cultural and intellectual belonging. It is part of the human being’s essence, shaping their relationship with the homeland as an emotional and psychological value, a space where affective and emotional energies flow, expressing their attachment and unity with it. Thus, the homeland is a mixture of feelings and emotions that requires complex analytical processes to be examined. Discussing the relationship between poetry and the homeland carries a distinctive feature, especially when the poetry in question is Yemeni poetry. The hardship that Yemen has experienced—and continues to experience—has led Yemeni poets to turn their attention to it, writing about it and narrating the details of its pain and fragmentation. The poet Zahir Habib is among contemporary Yemeni poets who have extensively addressed the theme of the homeland in his recently published collection entitled “Jirāḥ Muḍāraʿa”. In this collection, the theme of the homeland has become a striking and central image. In this study, we attempt to examine the theme of the homeland as it appears in “Jirāḥ Muḍāraʿa”, considering it an effective element in literary criticism and textual analysis. Through it, we aim to reach the structural patterns of the poems by identifying points of dissonance in order to uncover the underlying harmony. We also seek to relate this phenomenon to the poet’s psychological state, orientations, and views, since theme constitutes the most essential unit of analysis.